An analysis of some translation problems of terms from English to Xitsonga with special reference to South Africal law. - Nxumalo, Wendy Shihlamariso (My University, 2008)
The study analyses some of the translation problems of terms from English to Xitsonga, taking into consideration the translation work done thus far with special reference to South African law. The study is divided into six chapters: Chapter one is the introduction. It indicates the aim and rationale behind its study. It also highlights the methodology to be used, scope, terminological work done thus far and a brief definition of significant themes that are of importance to the study, which include “Terminology, Language for General Purpose, Language for Specific Purpose, Translation, Semantics and Indigenous law”. The chapter will also have a summary. Chapter two outlines some of the translation problems of terms from English to Xitsonga. In order to achieve this, the study will look into some of the translation work on terminology done thus far. A summary to the chapter will be given. Chapter three is about some of the terminology of the South African Law, where the translation problems outlined in chapter 2 will guide with the translation of the terminology of this law. These terms will be defined in English, summarised in Xitsonga which will then assist with the equivalents of these terms in Xitsonga. The chapter will also be summarised. Chapter four gives the summary of all the terms which have been used to bring forth this analysis, guided by the translation problems found in chapter 2. A summary to this chapter will be given. Chapter five is the general conclusion of the study and recommendations. Chapter six lists cited materials in the study.
Thesis (M.A.) --University of Limpopo, 2008.
Keywords: Translation problems; South African Law; Xitsonga; 418.02; Language translation